Bridging the knowledge-action gap: A framework for co-producing actionable knowledge - Räsänen, Aleksi; Sarkki, Simo; Haanpää, Olli; Isolahti, Maria; Kekkonen, Hanna; Kikuchi, Karoliina; Koukkari, Ville; Kärkkäinen, Katri; Miettinen, Janne; Mäntymaa, Erkki; Nieminen, Mika; Rahkila, Riina; et al. (Elsevier, 2024)
Rapidly increasing knowledge on environmental problems and their potential solutions is underused by policy and practice. This mismatch constitutes a knowledge-action gap. To bridge the gap, the concept of actionable knowledge has been proposed, which is often understood as outputs, data, policy briefs, or other types of products. We instead propose to understand actionable knowledge as a process that has (1) cumulative and stepwise, (2) iterative and cyclical, and (3) coevolutionary characteristics. These characteristics are often considered in isolation or even to be in contradiction with each other. We integrate these three characteristics in an analysis of transdisciplinary project developing a catchment-scale land use roadmap and catchment coordination in the Kiiminkijoki river catchment, northern Finland. Our analysis is based on four general phases in a knowledge co-production process (making sense together, knowledge validation, usable outputs, boundary spanning), which are concretized through nine practical steps. We find that collection, analysis, and usage of the knowledge has been even more important for action than the final output (i.e., the roadmap). Furthermore, the process of actionable knowledge does not end with the project but continues with negotiations to establish a catchment coordinator position. Our major finding is that there is no single point in time during a transdisciplinary project to bridge the knowledge–action gap but multiple planned and surprising opportunities emerge during the process. Overall, our approach contributes to advance sustainability transformations in catchment management and governance by understanding how transdisciplinary projects can initiate and are a part of evolving knowledge-action processes.
Keywords: actionable knowledge; catchment governance; knowledge co-production; river basin management; transdisciplinary research; usable knowledge